2016
DOI: 10.1016/j.bpj.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Shape Selection of Surface-Bound Helical Filaments: Biopolymers on Curved Membranes

Abstract: Motivated to understand the behavior of biological filaments interacting with membranes of various types, we employ a theoretical model for the shape and thermodynamics of intrinsically helical filaments bound to curved membranes. We show that filament-surface interactions lead to a host of nonuniform shape equilibria, in which filaments progressively unwind from their native twist with increasing surface interaction and surface curvature, ultimately adopting uniform-contact curved shapes. The latter effect is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…How does the intrinsic twist of MreB double protofilaments affect MreB conformation in vivo ? To answer this question, we utilized a coarse-grained model 28 in which an MreB double protofilament is represented as a beam, with its bending and twisting stiffness extracted from our all-atom MD simulations (Methods). Considering that the large turgor pressure across the bacterial cell envelope (∼1 atm 29 ) forces the membrane to adopt a shape matching that of the cell wall, we treated the membrane as a rigid cylindrical surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…How does the intrinsic twist of MreB double protofilaments affect MreB conformation in vivo ? To answer this question, we utilized a coarse-grained model 28 in which an MreB double protofilament is represented as a beam, with its bending and twisting stiffness extracted from our all-atom MD simulations (Methods). Considering that the large turgor pressure across the bacterial cell envelope (∼1 atm 29 ) forces the membrane to adopt a shape matching that of the cell wall, we treated the membrane as a rigid cylindrical surface.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the large turgor pressure across the bacterial cell envelope (∼1 atm 29 ) forces the membrane to adopt a shape matching that of the cell wall, we treated the membrane as a rigid cylindrical surface. We calculated the Hamiltonian for an infinitely long MreB beam with intrinsic twist and bend 28 , and identified the local twist and bend angles that minimize its energy (Methods, Fig. 4d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Within the cell, MreB can be either a helix or a ring. [3][4][5][6][7][8][9][10][26][27][28][29][30][31] It was found that MreB filaments have a persistence length 5 to 10 times larger than the bacterial cell size. 3,13 Consequently, the shape of the cell provides a strong constraint on the MreB filament.…”
Section: Introductionmentioning
confidence: 99%